2016
DOI: 10.1002/ccr3.543
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in a neonate with placental mesenchymal dysplasia

Abstract: Key Clinical MessageCauses of intrauterine fetal death (IUFD) are uncertain in most placental mesenchymal dysplasia (PMD) cases. Our case showed high α‐fetoprotein levels in the maternal circulation, markedly dilated subchorionic vessels, and neonatal hemoglobin concentration of 8.4 g/dL, suggesting that fetal anemia may explain some adverse outcomes in PMD pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Moreover, MSAFP levels might reflect the degree of placental vasodilation and fetal adverse outcomes; in PMD, fetal erythropoiesis might not adapt to the acute enlargement of the vascular bed, resulting in fetal anemia or FD 15 . In our study, nine patients in whom MSAFP was measured within a week before delivery.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, MSAFP levels might reflect the degree of placental vasodilation and fetal adverse outcomes; in PMD, fetal erythropoiesis might not adapt to the acute enlargement of the vascular bed, resulting in fetal anemia or FD 15 . In our study, nine patients in whom MSAFP was measured within a week before delivery.…”
Section: Discussionmentioning
confidence: 87%
“…The high MSAFP—the principal characteristic of PMD—is the consequence of an increased surface for transfer due to the enlarged placenta and the increased permeability of thin-walled vessels within the stem villi [ 46 , 47 ]. Moreover, the degree of adverse fetal outcomes might correlate with the MSAFP levels [ 46 ]; even in the absence of PMD, approximately 10% of fetuses carried by women with a persisting elevated AFP level ≥2.5 Multiple of the Median (MoM), die in utero [ 9 ]. In PMD, the fetal erythropoiesis might not adjust to the sharp increase in the vascular plate, leading to fetal anemia or adverse outcomes, such as fetal growth restriction, hydrops fetalis, or intrauterine fetal death (IUFD) [ 9 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the degree of adverse fetal outcomes might correlate with the MSAFP levels [ 46 ]; even in the absence of PMD, approximately 10% of fetuses carried by women with a persisting elevated AFP level ≥2.5 Multiple of the Median (MoM), die in utero [ 9 ]. In PMD, the fetal erythropoiesis might not adjust to the sharp increase in the vascular plate, leading to fetal anemia or adverse outcomes, such as fetal growth restriction, hydrops fetalis, or intrauterine fetal death (IUFD) [ 9 , 46 ]. In these cases, intensive monitoring of the Middle Cerebral Artery-Peak Systolic Velocity (MCA-PSV) using ultrasound may be helpful to avoid IUFD in some PMD pregnancies [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, PMD is found in 9% of uncomplicated pregnancies [3]. Moreover, several studies also reported abnormal neonatal outcomes such as aneuploidy, Beck-Wiedemann syndrome, hepatic tumor, and hematologic disorders [8][9][10][11][12][13]. Accordingly, prenatal ultrasound indication of thickened placenta with suspicion of placental hemorrhage or PMD should be considered as a high risk pregnancy, which needs close surveillance and follow-up.…”
Section: Discussionmentioning
confidence: 99%